A Reassessment of Two Theories of Pourshariatiʼs Thriple View in her “Decline and Fall of the Sasanian Empire: The Sasanian Parthian Confederacy and the Arab Conquest of Iran” - Yaser Malekzadeh; Sorour Khorashadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Parvaneh Pourshariati’s study, “Decline and Fall of the Sasanian Empire. The Sasanian-Parthian Confederacy and the Arab Conquest of Iran”, is a substantial investigation that offers a novel perspective supported by a great number of details and data from multiple disciplines. This book has received various receptions in the scholarship. The paper is dedicated to the reexamination of three conceptual constituents in the Pourshariati’s narrative: first, her master thesis concerning the confederation nature of the Sassanid state. Second, the religious-cultural differences among the Persians and the Parthians. Third, the chronology of the Futuh. Through a critical-analytic approach, the authors argue that opposing Pourshariati’s master thesis, there seem to be sequential periods of centralization and de-decentralization in the Sassanid Empire. Furthermore, we discuss that, in spite of Pourshariati’s interesting idea about the religious differences between Pārsīg and Pahlaw, her argument is not justified.